Influence of Optimization of Process Parameters on Threshold Voltage for Development of HfO2/TiSi2 18 nm PMOS - Atan N.; Ahmad I.; Majlis B.Y.; Azle M.F. (EDP Sciences, 2023)
Gate dielectrics; Hafnium oxides; Ion implantation; Ions; Manufacture; Taguchi methods; Threshold voltage; Compensation implantations; Fabrication process; Halo implantation; Ion implantation methods; Optimization of process parameters; Process parameters; Short-channel effect; Taguchi orthogonal arrays; Signal to noise ratio